Spin-orbital entangled liquid state in the copper oxide Ba3CuSb2O9. (10th October 2018) - Man, Huiyuan; Halim, Mario; Sawa, Hiroshi; Hagiwara, Masayuki; Wakabayashi, Yusuke; Nakatsuji, Satoru
Abstract: Structure with orbital degeneracy is unstable toward spontaneous distortion. Such orbital correlation usually has a much higher energy scale than spins, and therefore, magnetic transition takes place at a much lower temperature, almost independently from orbital ordering. However, when the energy scales of orbitals and spins meet, there is a possibility of spin-orbital entanglement that would stabilize novel ground state such as spin-orbital liquid and random singlet state. Here we review on such a novel spin-orbital magnetism found in the hexagonal perovskite oxide Ba3 CuSb2 O9, which hosts a self-organized honeycomblike short-range order of a strong Jahn–Teller ion Cu 2+ . Comprehensive structural and magnetic measurements have revealed that the system has neither magnetic nor Jahn–Teller transition down to the lowest temperatures, and Cu spins and orbitals retain the hexagonal symmetry and paramagnetic state. Various macroscopic and microscopic measurements all indicate that spins and orbitals remain fluctuating down to low temperatures without freezing, forming a spin-orbital entangled liquid state.